Advanced derivatives pricing and risk management theory, tools and hands-on programming application - Albanese, Claudio; Campolieti, Giuseppe (Amsterdam ; Boston : Elsevier Academic Press, 2006)
Written by leading academics and practitioners in the field of financial mathematics, the purpose of this book is to provide a unique combination of some of the most important and relevant theoretical and practical tools from which any advanced undergraduate and graduate student, professional quant and researcher will benefit. This book stands out from all other existing books in quantitative finance from the sheer impressive range of ready-to-use software and accessible theoretical tools that are provided as a complete package. By proceeding from simple to complex, the authors cover core topics in derivative pricing and risk management in a style that is engaging, accessible and self-instructional. The book contains a wide spectrum of problems, worked-out solutions, detailed methodologies and applied mathematical techniques for which anyone planning to make a serious career in quantitative finance must master. In fact, core portions of the books material originated and evolved after years of classroom lectures and computer laboratory courses taught in a world-renowned professional Masters program in mathematical finance. As a bonus to the reader, the book also gives a detailed exposition on new cutting-edge theoretical techniques with many results in pricing theory that are published here for the first time. *Includes easy-to-implement VB/VBA numerical software libraries *Proceeds from simple to complex in approaching pricing and risk management problems *Provides analytical methods to derive cutting-edge pricing formulas for equity derivatives.
Pricing theory -- Fixed-income instruments -- Advanced topics in pricing theory : exotic options and state-dependent models -- Numerical methods for value-at-risk -- Project : arbitrage theory -- Project : the Black-Scholes (lognormal) model -- Project : quantile-quantile plots -- Project : Monte Carlo pricer -- Project : the binomial lattice model -- Project : the trinomial lattice model -- Project : Crank-Nicolson option pricer -- Project : static hedging of barrier options -- Project : variance swaps -- Project : Monte Carlo value-at-risk for Delta-Gamma portfolios -- Project : covariance estimation and scenario generation in value-at-risk -- Project : interest rate trees : calibration and pricing.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Risk management; Derivative securities -- Prices; Electronic books